A simple model for damage analysis of a frame-masonry shear-wall system. (15th December 2017) - Di Nino, Simona; D'Annibale, Francesco; Luongo, Angelo
Abstract: This paper is aimed at evaluating dissipation and deformation capacities of frame-masonry shear-wall systems in post-cracking regime. A simple planar model consisting of a cracked masonry shear-wall, containing a centered window, confined on three sides by a portal frame, is formulated. Kinematics is linear and accounts for an "overall shear mode" and "local sliding modes", these latter describing relative motions among the cracked parts of the wall. A periodic horizontal force, roughly representative of the seismic actions, is acting at the top of the portal frame. An isotropic nonlinear damage law is adopted, and an Extended Galerkin-based variational formulation is followed to derive a low-dimensional discrete system. An ad-hoc resolution algorithm, based on a predictor-corrector scheme, is implemented, and numerical results discussed.